Analysis of transition metal content in glioblastoma reveals association between iron and survival - Ganesh Shenoy; Aurosman Sahu; Madison Kuhn; Vladimir Khristov; Madison Heebner; Hannah Wilding; Taylor Clegg; Debarati Bhanja; Quinn Wade; Laura J. Liermann; Dongxiang Wang; Nataliya Smith; et al. (Translational Oncology, 2025)
Introduction: Little is known about the role of transition metals in glioblastoma progression. Here we investigated whether transition metal content is associated with glioblastoma outcomes. Methods: Tumor samples were obtained from 37 newly diagnosed patients with glioblastoma, 21 of which had matched plasma. Iron, zinc, manganese, and copper content in those samples was quantified via inductively-coupled mass spectrometry or atomic emission spectrometry, and subsequently analyzed for associations with overall survival. Multiplexed immune profiling was performed to determine whether transition metal content was associated with altered cytokine profiles. Results: Higher plasma iron levels were strongly associated with prolonged survival (Kaplan-Meier analysis: 30.15 months vs. 12.43 months, P = 0.0036; Multivariate Cox regression analysis: HR: 0.79 [0.64 – 0.97], P = 0.03). Zinc, manganese, and copper concentration in plasma or tumor and iron in tumor were not significantly associated with overall survival. Immune profiling of plasma and tumor samples revealed that plasma iron correlated with plasma IFN-β concentration (R = 0.63, P = 0.0057) in patients with glioblastoma. No correlation of plasma iron and IFN-β was observed in age- and sex- matched healthy individuals (R = -0.15, P = 0.153). Plasma transition metal concentration did not correlate with tumor transition metal concentration. Within tumors, manganese and zinc were correlated (R = 0.52, P = 0.0048) as well as copper and zinc (R = 0.36, P = 0.038). Conclusions: Plasma iron is associated with survival in glioblastoma patients and may serve as a prognostic marker. The mechanisms underlying this association require further study.